Legal entities as subjects of environmental relations - Malinovskaya, Anna I. (Journal of the Belarusian State University. Law, 2020)
The legal status of entities engaged in economic activity is analized. Their basic rights and obligations in the field of environmental protection are considered. It is concluded that the legal entity carrying out economic activities is not entitled to a favorable environment. Recommendations were made for improving the environmental and legal regulation of the activities of legal entities carrying out economic activities.
Keywords: legal entity; subjects; environmental rights; environmental obligations; favorable environment; environmental requirements; environmental powers; principles; economic activity; agricultural activity; environmental management; agricultural legislation